Relationship of Follicular Size with Dimensions of Genital System of Female Iraqi Buffaloes (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2019)
The present study has been conducted at laboratories of department of animal production techniques, AI-Musaib Technical College during the period extended from march 2014 to march 2015 to determine relationship of follicular size with dimensions of genital system of female Iraqi buffaloes. One hundred and twenty genital system of adults non- pregnant buffaloes slaughtered at abattoirs of Babylon province were collected at the time of slaughter and transported to the laboratory within 2 hours. The. A total of 240 ovaries were removed and collected. The diameter of the ovarian follicles were measured, divided into three categories, small (2-5 mm), medium (6-10 mm) and large (11-20 mm) . The results showed that the ovaries in local buffaloes appear as oval , light pinkish , firmed consistency and smooth. A significant increased (P